Pembelajaran STEM di NYPi Singapura sebagai Inspirasi Pendidikan di Indonesia - Adik Kristien (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
Education and training for the application of the STEM approach in Singapore's Nanyang Polytechnic are carried out by the Ministry of Education and Culture of the Republic of Indonesia in order to implement Presidential Instruction No. 9 of 2016 concerning Revitalization of Vocational High Schools in the Framework of Improving the Quality and Competitiveness of Indonesian Human Resources. By observing and understanding the education system, the learning system, the application of the STEM approach, the use of varied and student-centered learning models, an effective and efficient assessment system, and STEM products in Singapore can be a source of inspiration that can be applied in Indonesia.